Level of knowledge of Pantawid Pamilyang Pilipino Program pupil beneficiaries its effect to their academic performance - Villamor, Eva E.; Adanza, Lito S. (2016)
Pantawid Pamilyang Pilipino Program was implemented in the Philippines to break intergenerational cycle of poverty. However, there were limited studies on how the knowledge of the pupil beneficiaries on the program affects their performance in Maasim, Sarangani. For this reason, this study was ventured to determine the level of knowledge of Pantawid Pamilyang Pilipino Program pupil beneficiaries and its effects to their academic performance. Correlational method of research was used. One hundred six (106) pupil beneficiaries were identified as respondents. An adopted and modified questionnaire was used. The findings revealed that pupil beneficiaries Agree (M=3.86) they have knowledge about the conditions, benefits and implementation of the program. In addition, the level of knowledge of the pupil beneficiaries is significantly related to their academic performance. Result of this study may serve as basis for program implementers on how to enhance information and education campaign in order to improve academic performance of the pupil beneficiaries.
Keywords: Family development program (Pantawid Pamilya Pilipino Program); Pantawid Pamilya Pilipino Program; Mindanao studies